Re-scan confocal microscopy (RCM) improves the resolution of confocal microscopy and increases the sensitivity. (25th January 2017) - De Luca, Giulia; Breedijk, Ronald; Hoebe, Ron; Stallinga, Sjoerd; Manders, Erik
Abstract: Re-scan confocal microscopy (RCM) is a new super-resolution technique based on a standard confocal microscope extended with a re-scan unit in the detection path that projects the emitted light onto a sensitive camera. In this paper the fundamental properties of RCM, lateral resolution, axial resolution and signal-to-noise ratio, are characterized and compared with properties of standard confocal microscopy. The results show that the lateral resolution of RCM is ~170 nm compared to ~240 nm of confocal microscopy for 488 nm excitation and 1.49 NA. As the theory predicts, this improved lateral resolution is independent of the pinhole diameter. In standard confocal microscopy, the same lateral resolution can only be achieved with an almost closed pinhole and, consequently, with a major loss of signal. We show that the sectioning capabilities of the standard confocal microscope are preserved in RCM and that the axial resolution of RCM is slightly better (~15%) than the standard confocal microscope. Furthermore, the signal-to-noise ratio in RCM is a factor of 2 higher than in standard confocal microscopy, also due to the use of highly sensitive modern cameras. In case the pinhole of a confocal microscope is adjusted in such way that the lateral resolution is comparable to that of RCM, the signal-to-noise ratio in RCM is 4 times higher than standard confocal microscopy. Therefore, RCM offers a good alternative to standard confocal microscopy for higher lateral resolution with the main advantage of strongly improved sensitivity.